Meningkatkan Hasil Belajar IPS Siswa Kelas VIII A SMP Negeri 5 Kendari melalui Strategi Make a Match - Sitti Maryam (Jurnal Didaktika Pendidikan Dasar, 2022)
Several causal factors to students’ low achievement are among others density and large coverage of social science learning matterials (consisting of history, sociology, economics, and geography), students’ lack of learning skills, and teacher’s inadequate method of teaching. The problem of students’ low achievement on social science subject also occurred at SMP Negeri 5 Kendari. This study applied classroom action research method with cyclical model. The data were collected by means of observation and achievement testing techniques. The data were then analysed by means of interactive model from Milles and Hubberman. On the basis of testing and learning reflection results, it was showed that (a) the use of make a match strategy really improved students’ learning achievement on social science; (b) It really improved students’ active participation during the teaching and learning process; (3) The number of students who achieved marks above the minimal efficacy mark criterion was above 85%; and (4) The students showed their positive perception towards their learning activities under make a match strategy.